Limited Vitrectomy versus Complete Vitrectomy for Epiretinal Membranes: A Comparative Multicenter Trial. (23rd October 2020) - Forlini, Matteo; Date, Purva; D'Eliseo, Domenico; Rossini, Paolo; Bratu, Adriana; Volinia, Andrea; Neri, Giovanni; Verdina, Tommaso; Carbotti, Maria Rosaria; Cavallini, Gian Maria; Sborgia, Luigi; Galeone, Alessandra; et al.
Abstract : Purpose . To evaluate whether limited vitrectomy is as effective as complete vitrectomy in eyes with epiretinal membrane (ERM) and to compare the surgical times and rates of complications. Methods . In this multicentre European study, data of eyes with ERM that underwent vitrectomy from January 2017 to July 2018 were analyzed retrospectively. In the limited vitrectomy group, a posterior vitreous detachment (PVD) was induced up till the equator as opposed to complete PVD induction till the vitreous base in the comparison group. Incidence of iatrogenic retinal breaks, retinal detachment, surgical time, and visual outcomes were compared between groups. Results . We included 139 eyes in the analysis with a mean age being 72.2 ± 6.9 years. In this, sixty-five eyes (47%) underwent limited vitrectomy and 74 eyes (53%) underwent complete vitrectomy. Iatrogenic retinal tears were seen in both groups (5% in limited vitrectomy versus 7% in complete vitrectomy, p = 0.49 ). Retinal detachment occurred in 2 eyes in the limited vitrectomy group (3%) compared to none in the complete vitrectomy group (p = 0.22 ). Best-corrected visual acuity (BCVA) and central macular thickness improved significantly with no intergroup differences (p = 0.18 ). Surgical time was significantly shorter in the limited vitrectomy group with 91% surgeries taking less than 1 hour compared to 71% in the complete vitrectomy group (p < 0.001 ). Conclusion . A limited vitrectomy is a time-efficient and effective surgical procedure for removal of epiretinal membrane with no additional complications.